Pengaruh Penggunaan Anggaran dan Gaya Manajemen Terhadap Hubungan antara Perubahan Strategik dan Kinerja Organisasi - Siti Musyarofah (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2004)
This research examines the interaction influence of strategic changes with the budget use and management style on the performance of organization. The questionnaire sent to general manager of corporations listed on Standard Trade & Industry Directory Indonesia 2002th published by Kompas, PT. Forty two answers of respondent were analyzed with Moderated Regression Analy¬sis (MRA). The result of the analysis did not support to the two formulated hypotheses. It shows that the inter¬action influence between strategic changes with the budget use style and management style did not statistically improve the performance of the organization. In other words, strategic changes will have a positive influence on the performance when the corporation used unproved budget interactively.Keywords: strategic change, budget use, management style and performance of organization.